Dimensi Psikologis dalam Ibadah-Ibadah Agama Islam - Zuhriati; Kinana Dwinta Sukma; Sasmitro Anggoro; Meilani; Dayana Sabila; Ramadan Lubis (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This research aims to examine the impact of fasting and Hajj on psychological aspects and individual personality formation. The background to this research is the importance of understanding how religious rituals can have a profound influence on daily life, especially in the context of controlling emotions, decision making, and character formation. This study focuses on the experiences of a basic food trader, Ahmad Fauzan, who is fasting, and a housewife, Siti Sahara, who has completed the Hajj, to illustrate the role of worship in changing an individual's personality and psychological well-being. This research uses a qualitative approach with in-depth interview methods as the main technique for collecting data. Informants were selected purposively based on suitability for the research objectives. Interviews were conducted to understand their subjective experiences during fasting and Hajj. Ahmad Fauzan revealed that fasting helps him manage emotions, such as increasing patience and gratitude, as well as forming a personality that is more honest and surrenders to Allah. Siti Sahara, through her Hajj experience, experienced significant spiritual transformation, such as emotional control, deep introspection, and resilience in facing life's challenges. The research results show that fasting and Hajj have a significant impact on psychological well being and individual personality formation. Ahmad and Siti showed positive changes in terms of patience, honesty, gratitude and spiritual steadfastness. The conclusion of this research is that religious worship functions not only as a spiritual ritual but also as a tool to build character, improve mental health, and create better relationships with others and God.